Unraveling the obstacles to transform agro-wastes into value-added bioproducts: Implications for sustainability - Khandakar Shamit Raja; Ayesha Maliha; Sourav Paul; Md Shihab Shakur; A.B.M. Mainul Bari (Sustainable Operations and Computers)
The global population and economy heavily rely on agriculture. Various agricultural processes generate copious amounts of waste. Effectively managing these agricultural wastes, or agro-waste, is necessary to mitigate environmental pollution, reduce greenhouse gas emissions, and achieve carbon neutrality and sustainability. This has led to increased scientific interest in converting agro-waste into value-added bioproducts. However, the obstacles that hinder the adoption and implementation of this technology have still not been explored much. This study, therefore, employs a comprehensive novel integrated multi-criteria decision-making (MCDM) approach, combining the Interval-Valued Type 2 Intuitionistic Fuzzy (IVT2IF) theory with the Decision-Making Trial and Evaluation Laboratory (DEMATEL) method to evaluate the obstacles. This approach aims to identify, rank, and analyze the interrelationships among the obstacles hindering agro-waste conversion into value-added bioproducts. Through literature review and expert validation, 17 obstacles were identified to be analyzed using the IVT2IF-DEMATEL method. The study’s findings suggest that ''uncertainty about the return on investment (ROI) is the most influential obstacle, with a prominence value of 12.17, likely owing to its direct influence on investment decisions and the economic viability of agro-waste projects, followed by ''lack of regulatory and legislative assistance'' (12.02) and ''necessity of a high initial investment'' (11.77). The study’s findings have the potential to provide policymakers and decision-makers valuable insights for shaping investment decisions and developing effective long-term plans to facilitate and incentivize green agro-businesses that utilize agro-wastes and thus promote carbon neutrality and sustainable development in the agriculture-based industrial sectors.